Investing in the Early Years During COVID-19 - World Bank (World Bank, Washington, DC, 2020)
Young children need comprehensive nurturing care which includes good health, adequate nutrition, early learning opportunities, responsive caregiving, and safety and security. Severe, lifelong impacts can result from deprivations during the early years if children do not have these critical inputs to ensure optimal child development. The World Bank’s Investing in the Early Years framework lays out three pillars to ensure children reach their full potential: i. Children are healthy and well-nourished, especially in the first 1,000 days ii. Children receive early stimulation and learning opportunities and iii. Children are nurtured and protected from stress. In the following three pages, we set out specific risks that children face under each of these pillars due to the COVID-19 (Coronavirus) crisis, together with response options, potential platforms and country examples. While health and nutrition are key elements of the COVID-19 (Coronavirus) emergency response and are more likely to be addressed immediately, empowering parents to provide warm and responsive caregiving and ensuring safety and security of young children and early learning opportunities for young children is essential and risks falling through the cracks.